Beta 2 glycoprotein I and neutrophil extracellular traps: Potential bridge between innate and adaptive immunity in anti-phospholipid syndrome - Grossi, Claudia; Capitani, Nagaja; Benagiano, Marisa; Baldari, Cosima Tatiana; Della Bella, Chiara; Macor, Paolo; Tedesco, Francesco; Borghi, Maria Orietta; Maugeri, Norma; D’Elios, Mario Milco; Meroni, Pier Luigi (Frontiers in Immunology, 2023)
Antiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by recurrent vascular thrombosis and miscarriages in the absence of known causes. Antibodies against phospholipid-binding proteins (aPL) are pathogenic players in both clotting and pregnancy APS manifestations. There is sound evidence that antibodies specific for beta2 glycoprotein I (β2GPI) trigger thrombotic and pregnancy complications by interacting with the molecule on the membranes of different cell types of the coagulation cascade, and in placenta tissues. In addition to the humoral response against β2GPI, both peripheral and tissue CD4+β2GPI-specific T cells have been reported in primary APS as well as in systemic lupus erythematosus (SLE)-associated APS. While adaptive immunity plays a clear role in APS, it is still debated whether innate immunity is involved as well. Acute systemic inflammation does not seem to be present in the syndrome, however, there is sound evidence that complement activation is crucial in animal models and can be found also in patients. Furthermore, neutrophil extracellular traps (NETs) have been documented in arterial and venous thrombi with different etiology, including clots in APS models. Keeping in mind that β2GPI is a pleiotropic glycoprotein, acting as scavenger molecule for infectious agents and apoptotic/damaged body constituents and that self-molecules externalized through neutrophil extracellular traps (NETs) formation may become immunogenic autoantigens, we demonstrated β2GPI on NETs, and its ability to stimulate CD4+β2GPI-specific T cells. The aim of this review is to elucidate the role of β2GPI in the cross-talk between the innate and adaptive immunity in APS.